Fisherman Competency Study on Fishing Business Units on Pole and Line Based on SKKNI and STCWF-1995 in Sikka Maumere Regency, East Nusa Tenggara - Zulkarnaen, Muhammad Sufi; Mallawa, Achmar; Purwangka, Fis (International Journal of Environment, Agriculture and Biotechnology, 2021)
One of fishermen's problems is skills and knowledge. The skills and knowledge of fishermen are obtained from a learning process that is hereditary. Fisherman competency standards are important in order to improve work safety and fishing business. This study aims to evaluate the competence of pole and line fishermen based on SKKNI 2013-298 (competence units for operating huhate (pole and line)), SKKNI 2005-191 PRK.NP03002.01, and STCW-F 1995 Resolution 3 in Sikka Maumere Regency, East Nusa Tenggara and the suitability of fishermen's competency standards in SKNNI and STCW-F 1995. Fishermen's competency data were obtained through observation and in-depth interviews with selected respondent fishermen and then analyzed based on these two standards. National fishermen's competency standards are also evaluated for conformity to international standards. The amount of weighting is determined based on the level of importance of each of the existing performance criteria. The assessment criteria for competency elements use a score scale of 1-4. The total value of the weights is 10. The total value of x weights is 40, then multiplied by 100%. Obtaining the suitability value of each performance criterion can show the level of conformity of the fishermen's competence with competency standards. The results showed that (1) the competence of fishermen based on the 2005-191 SKKNI was not suitable (conformity value interval <50%), while based on the 2013-298 SKKNI it was quite appropriate (conformity value interval between 50-75%). (2) Fishermen are still not suitable (conformity value interval <50%) to the implementation of STCW-F 1995 resolution 3. (3) The basic competency units in SKKNI 2005-191 and SKKNI 2013-298 are divided into 7 competency units. Meanwhile, in STCW-F 1995 became an integral part of the competency unit as a basic level safety training for fishermen.